A Qualitative Study to Explore the Role of Health Workers in Reducing Smokeless Tobacco Consumption in India - Neha Mehta (Journal of Health Technology Assessment in Midwifery, 2023)
India is one of the largest smokeless tobacco consumers globally, leading to devastating health consequences. However, smokeless tobacco still remains poorly understood. Health workers have an essential role in curbing this rise in consumption by offering smokeless tobacco prevention advice. A better understanding of health workers knowledge and practice at offering preventative advice will help strengthen tobacco policies. This study aims to explorethe role of HWs offering SLT prevention advice by identifying facilitators for and barriers against implementation of this opportunistic strategy.Â Health workers were recruited through purposive sampling and sixteen participants took part in semi-structured online interviews. Data was transcribed verbatim and analysed through thematic analysis. Health workers stated that training was the greatest facilitator but also greatest barrier to providing smokeless tobacco prevention advice. They also thought that training during university was inadequate and external training sources were more beneficial to providing prevention advice. Smokeless tobacco training of a high standard is a major facilitator and needs providing during university and post-gradation. Smokeless tobacco needs prioritisation over smoking tobacco policies in India and stakeholders need to come together to tackle this multi-factorial problem.